Dental service voucher for adults: patient experiences in Finland - Ilonen Susanna; Ylönen Sabiina; Kaila Minna; Lahti Satu; Hiivala Nora (TAYLOR & FRANCIS LTD, 2025)
Objective
To investigate how patients experienced a new dental service voucher, what influenced the patient experience, and the use of such vouchers.
Materials and methods
An SMS-linked patient survey was sent to all patients (n = 1,000) that had received the voucher. The survey consisted of 23 questions (20 multiple choice, 3 open-ended), included themes like access to treatment, use of the voucher, and patient experience. Statistical analyses included Chi-square, Fisher’s exact, Mann-Whitney U tests, and Spearman’s rank correlation.
Results
The response rate was 25.7%. Patient experience was on average very good. Of the respondents, 148 (57.6%) reported that the voucher was very simple to use, 160 (62.3%) considered that they were helped very well, and 149 (58%) would have very willingly used a voucher again. Those who used the voucher reported an overall better patient experience, as did those with good oral health. Of those reporting unused service vouchers, 14 (67%) preferred to use the public oral health care services instead.